Novel Treatment Approaches for Locally Advanced Pancreatic Cancer - Gorovets, Daniel; Saif, Muhammad Wasif; Huber, Kathryn (JOP. Journal of the Pancreas, 2014)
Despite decades of research, pancreatic cancer remains essentially incurable for patients with unresectable tumors. In the United States, most patients with locally advanced pancreatic cancer are treated with chemotherapy alone or combined with conventionally fractionated radiotherapy. Regardless of the treatment strategy, average survival for these patients is less than 1 year, indicating that the current approaches are indisputably inadequate. For locally advanced pancreatic cancer patients, effective local-regional control is not only crucial for any hope at long-term survival, but also for symptom management. The aim of this paper is to highlight abstracts from the 2014 ASCO Gastrointestinal Cancers Symposium that demonstrate the use of novel local-regional therapies in locally advanced pancreatic cancer. Abstracts #317, #328, and #361 describe their results with an advanced method of delivering radiation called stereotactic body radiation therapy (SBRT). In these studies, patients treated with combined chemotherapy and SBRT had exceptional local control rates and acceptable toxicity. An innovative alternative to radiation for local-regional treatment is presented in Abstract #270. This study shows encouraging results from a phase I investigation of a regionally delivered siRNA that targets the K-rasG12D mutation. Investigation of novel approaches such as those presented here holds the greatest promise for improving treatment of this deadly disease. Image: Tufts Medical Center. Boston, MA, USA